A Priestly Approach to Environmental Theology: Learning to Receive and Give Again the Gifts of Creation - Wirzba, Norman (Dialog, 2011)
A priestly sensibility is here presented as a way to characterize humanity's place in creation. Sacrifice, asceticism, and gratitude are described as three distinct and practical modalities of a priestly life that contribute to the care and celebration of creation. While a priestly understanding is often associated with Orthodox environmental theology, it has the potential to inform environmental theology broadly construed.